Benefit from regular versus leakage-related exchange of voice prostheses in patients post-laryngectomy considering complication rates and patient satisfaction feedback—a randomized case−controlled trial - Żurek, Michał; Czesak, Małgorzata; Majszyk, Daniel; Rzepakowska, Anna (Frontiers in Oncology, 2025)
ObjectiveThe complications related to voice prosthesis usage substantially affect the physical and social functioning of patients after total laryngectomy, which influences their quality of life. Leakage dysfunction is the most common, causing uncertainty and requiring unscheduled hospital visits. Our study was designed to estimate the benefit of regular versus leakage-related replacement of the voice prosthesis. Study Design. Randomized case−controlled trials. Setting. Tertiary hospital.MethodsThe study included patients who underwent total laryngectomy with primary voice prosthesis insertion between 2020 and 2021 and were randomly assigned to one of two arms: regular exchange (REA) every 3 months or leakage-dependent exchange (LEA). The control treatment was continued for 12 months. The primary outcome measure was the comparison of complication rates in both arms, including periprosthetic leakage, granulation or atrophy of mucosa around the fistula, and dislocation of the prosthesis. The secondary outcome measures were the mean number of exchanges per year and patient satisfaction.ResultsThirty-six patients continued the study according to the protocol, with 16 in REA and 20 in LEA. A total of 153 voice prostheses were replaced during the study period, including 98 in REA and 55 in LEA. Comparative analysis of REA and LEA revealed a significantly longer time between replacements in the LEA group (p = 0.023) and a significantly lower rate of complications in the REA group (p = 0.029). Periprosthetic leakage was the most common complication associated with the use of voice prostheses, occurring in 3.06% of patients in REA and 9.09% in LEA, but this difference was statistically insignificant (p = 0.137). The analysis of factors predisposing patients to leakage failure revealed that treatment schemes, concomitant diseases, dental conditions, and diet or alcohol consumption significantly affect the longevity of voice prostheses. The relative and absolute risks (RRR and ARR) of complications in the REA group were reduced by 69.39% and 13.88%, respectively. The number of replacements (NNTs) that should be performed in the REA scheme to prevent one complication over the LEA scheme is 721.ConclusionThe replacement of regular voice prostheses improved the overall complication rate over the scheme based on leakage demand; however, it did not yield superior benefits in terms of patient satisfaction or economic aspects.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT04268459, identifier NCT04268459.